Nicotine use in individuals with schizophrenia and its relation with clinical severity - Sharma, Bipul; Pathak, Kangkan; Nath, Subhashish; Mukherjee, Diptadhi (Asian Journal of Medical Sciences, 2022)
Background: Schizophrenia is a major psychiatric disorder with diverse clinical presentations and comorbidities. Comorbid nicotine use worsens the clinical symptomatology, predisposes the individuals to other chronic illnesses, and is associated with poorer outcomes in schizophrenia. It is thus clinically essential to assess the presence of tobacco use, the severity of nicotine dependence, and its correlation with psychopathology in patients with schizophrenia. Aims and Objectives: (i) To describe the pattern of tobacco use and severity of nicotine dependence in schizophrenia patients. (ii) To compare the socio-demographic variables and symptom severity of schizophrenia between tobacco users and non-users. (iii) To determine the correlation between the severity of nicotine dependence and clinical and nicotine related variables in patients of schizophrenia. Materials and Methods: It was a cross-sectional observational study conducted in a tertiary care level psychiatric hospital in the northeast of India. The study included 100 male schizophrenia patients. Fagerstrom Test for Nicotine Dependence (FTND) and FTND - Smokeless Tobacco, and the Positive and Negative Syndrome Scale five-factor model was used for assessment of the severity of nicotine dependence and symptoms of Schizophrenia, respectively. Results: 70% of the study sample used some form of tobacco. The severity of nicotine dependence was significantly higher in patients using both forms of tobacco. Tobacco use was significantly associated with lower educational status, employment status, and positive symptoms of Schizophrenia. Finally, the severity of nicotine dependence was significantly correlated with the severity of positive and emotional symptoms of schizophrenia. Conclusion: Higher positive and emotional symptoms of schizophrenia predicted severity of nicotine use. Study needs to be replicated in larger population of patients suffering from schizophrenia.